Prognostic factors for very early recurrence after neoadjuvant treatment and curative resection in pancreatic ductal adenocarcinoma - Leonhardt, Carl-Stephan; Narbekovas, Klaudia; Qadan, Motaz; Sahora, Klaus; Warshaw, Andrew L.; Prager, Gerald; Ferrone, Cristina R.; Lillemoe, Keith D.; Schindl, Martin; Strobel, Oliver; Fernández-del Castillo, Carlos; Hank, Thomas (Surgery, 2025)
Introduction - Very early recurrence in pancreatic ductal adenocarcinoma has been defined as recurrence ≤3 months after resection. Besides others, neoadjuvant treatment is delivered based on the assumption of preoperative eradication of micrometastasis as well as local downstaging. Prognostic factors of very early recurrence after neoadjuvant treatment remain largely unexplored. - Methods - All patients who underwent resection for pancreatic ductal adenocarcinoma after neoadjuvant treatment were identified from 2 institutional databases. Clinicopathologic data and demographics were extracted. Univariable and multivariable logistic regression modeling was performed. Multicollinearity was assessed with a variance inflation factor. - Results - After excluding patients who died within 90 days postresection and CA19-9 nonsecretors, 305 patients remained. A total of 178 (58.4%) patients received FOLFIRINOX, 39 (12.8%) received gemcitabine-based neoadjuvant treatment and 88 (28.9%) received various combinations. Pancreatic head resection was performed in 240 (78.7%) patients, whereas 65 (21.3%) underwent distal or total pancreatectomy. In total, 28 (9.1%) patients experienced recurrence ≤3 months. Median overall survival was 6 months (95% confidence interval: 5-32 months) in patients with very early recurrence, compared with 40 months (95% confidence interval: 32-60 months) in the remaining cohort (P < .0001). In multivariable regression analysis, positive lymph node status was associated with very early recurrence (odds ratio: 2.57, 95% confidence interval: 1.15-5.8). Notably, no association with R status, type of neoadjuvant treatment, or preoperative CA19-9 levels was detected. - Conclusion - Positive lymph node status is an independent prognostic marker for very early recurrence after neoadjuvant treatment, indicating that these patients require closer follow-up and may benefit from additional or early initiation of adjuvant therapy.